Konsep Sifat-sifat Allah: Analisis dan Perbandingan di Antara Aliran Mu’tazilah dan Asya’irah - Ismail, Ahmad Zuhdi (Jurnal Usuluddin, 1998)
The aim of this paper as its title indicates, is to investigate of Muslim theological doctrine, the attributes of God. The main discussions focuses on the sifat and dzat, the most controversial issues among the mutakallimun. Also discussed are the concept of the attributes of ideas (Sifat al-Ma’ani) such as Power, Knowledge, Will etc.